The Role of the Palangkaraya Diocese Church in Overcoming the Bad Impact of Environmental Exploitation Along the Kahayan River, Central Kalimantan - Adinuhgra, Silvester; Gaol, Erly Lumban (Journal of Social Science Utilizing Technology, 2024)
Background. This research starts from concerns about the area along the Kahayan River, Central Kalimantan. From upstream to downstream, the river area is being heavily exploited, in the form of illegal gold mining carried out by the people themselves. The impacts are quite worrying, such as serious forest damage, polluted river water, people losing land for farming, rubber plantations being destroyed to make way for mining sites, and the loss of livelihoods for fishermen (river fishers). Purpose. The aim of this research is to explore the role or participation of the Palangkaraya Diocese Catholic Church in responding to and overcoming the negative impacts of environmental exploitation along the Kahayan River. Method. This research uses a qualitative approach method. The research locations are in Sepang District, Gunung Mas Regency and Banama Tingang District, Pulang Pisau Regency. Our informants: Mining Community, Catholic Church Hierarchy, Central Kalimantan Environmental Service, Gunung Mas and Pulang Pisau government officials, and local traditional leaders. Results. The results of this research found that the Palangkaraya Diocese Church has great potential in overcoming the negative impacts of environmental exploitation on the Kahayan River. Through outreach, awareness campaigns and religious teachings, the Church makes people aware of the importance of environmental conservation. As a facilitator, the Church bridges collaboration between government, communities and organizations for environmental preservation. Financial support and resources from the congregation are also considered important elements. With these steps, the Church plays a strategic role in protecting the environment and collective prosperity. Conclusion. The Palangkaraya Diocese Church plays an important role in overcoming the impacts of environmental exploitation on the Kahayan River by integrating social teachings, building collaboration, and raising support for environmental preservation and community welfare.